2005
DOI: 10.1016/j.optcom.2005.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of stimulated Brillouin scattering effects in radio-over-fiber distribution systems

Abstract: Stimulated Brillouin Scattering (SBS) imposes a limitation on the transmitted power in radioover-fiber (RoF) distribution systems. By employing an optical filter at the transmitter that converts the optical microwave signal to Single Side Band (SSB) format, in order to overcome dispersive fading, it is also possible to reduce the effect of SBS on system performance. In this paper the authors compare the cases of filtering the optical microwave signal at the transmitter or the remote site of a radio-over-fibre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As the bandwidth of the scattered wave due to SBS is smaller (≥25 MHz) and it also distorts the signal of individual channels [10]. Hu et al (2005) studied the SBS effect on the radio-overfiber (RoF) distribution systems.…”
Section: Various Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the bandwidth of the scattered wave due to SBS is smaller (≥25 MHz) and it also distorts the signal of individual channels [10]. Hu et al (2005) studied the SBS effect on the radio-overfiber (RoF) distribution systems.…”
Section: Various Methodsmentioning
confidence: 99%
“…Hu et al (2005) studied the SBS effect on the radio-overfiber (RoF) distribution systems. They demonstrated that the modulation depth of the optical micro-wave signal can suppress the SBS effect.…”
Section: Various Methodsmentioning
confidence: 99%
“…where α is the attenuation coefficient (0.2 dB∕km) and L is the length of the fiber (varied from 5 to 100 km). 27 This nonlinear effect will produce mm-wave signals by the heterodyning with the laser source signals. The optical heterodyning technique is generating mm-waves that depend on the principle of combining two optical signals in a photodiode (PD).…”
Section: System Principle and Architecturementioning
confidence: 99%
“…2 However, the transmission of spectrally pure, high optical energy through an optical medium requires the consideration and management of nonlinear effects, such as stimulated Brillouin scattering ͑SBS͒. 3 The influences of SBS on optical transmission systems performance and resultant systems impairments is a subject of continued interest and research, 4,5 as photonic based systems become the primary transmissions medium for an increasing number of diverse applications, such as radio over fiber, 6 data synchronizing and buffering, 7 and higher speed telecommunications, to support new domestic services. 8 This also leads to the development of new subsystem components, such as high-Q passband filters, 9 Raman fiber lasers, 10 and erbium doped fiber lasers.…”
Section: High Performance Laser Linewidth Broadening For Stimulated Bmentioning
confidence: 99%